Appreciation and Task Handover Ceremony of Registrar - Nor Salwana, Mohammad Idris (2021)
PEKAN, 18 March 2021 - Universiti Malaysia Pahang (UMP) organised an appreciation ceremony for Associate Professor Dr. Mohd Ridzuan Darun, who had assumed the responsibility as Registrar/Chief Operating Officer for two years from 15 March 2019 to 14 March 2021.